1961
DOI: 10.1161/01.res.9.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Extrinsic Cardiac Denervation by Regional Neural Ablation

Abstract: A technique for complete extrinsic denervation of the heart by the ablation of neural structures in the mediastinum is described. The completeness of denervation was verified by direct electrical stimulation of the main vagal and sympathetic trunks. Total deple tion of myocardial catecholamines followed the procedure in chronic survivors. Animals prepared in this manner are useful in the study of the neurologically isolated heart and simulate this aspect of the problem of cardiac transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1963
1963
1977
1977

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…ported that regional neural ablation resulted in depleted norepinephrine stores in the dog heart. However, shamoperated controls in the studies of Cooper et al 15 and Chidsey et al 16 showed no significant differences in cardiac norepinephrine concentration from that found in normal dogs. The same observation has been made in the guinea pig.…”
Section: Pure Control Vs Sham-operated Controlsmentioning
confidence: 79%
See 2 more Smart Citations
“…ported that regional neural ablation resulted in depleted norepinephrine stores in the dog heart. However, shamoperated controls in the studies of Cooper et al 15 and Chidsey et al 16 showed no significant differences in cardiac norepinephrine concentration from that found in normal dogs. The same observation has been made in the guinea pig.…”
Section: Pure Control Vs Sham-operated Controlsmentioning
confidence: 79%
“…Thus, unoperated cats were considered suitable for control of experimental mechanical properties in our investigation. Consideration was given to the question of myocardial norepinephrine concentration since an earlier study 15 re- Data are expressed as mean ± SEM. Cardiac index was determined in three cats in each group.…”
Section: Pure Control Vs Sham-operated Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic total denervation of the heart results in profound depletion of cardiac NE stores 6 and provides an opportunity to study the effects of digitalis 326…”
Section: Additional Abstract Reserpine Strophanthidinmentioning
confidence: 99%
“…Remarkable depletion of the cardiac catecholamines caused by the stellate ganglionectomy in the cat (11) suggests the dominant participation of the post ganglionic fibers originating in, or craniad to, the stellate ganglion, to the sympathetic innervation on the heart. In the dog, on the other hand, cardiac catecholamines are hardly depleted by bilateral resection of the stellate ganglion and thoracic sympathetic chain and ganglia, but depleted by extensive resection of the nerve plexus adjacent to the heart (12). On the basis of the physiological studies, Pannier (13) has indicated that the sym pathetic cardiac accelerance nerves of the dog, at least in some part, pass through the stellate ganglion without changing neuron.…”
mentioning
confidence: 99%